P591 Gastroenterologist performed point-of-care gastrointestinal ultrasound improves patient understanding of disease activity, symptomatology, management decisions and clinical outcomes. (16th January 2018) - Friedman, A; Asthana, A; Knowles, S; Robbins, A; Gibson, P
Abstract: Background: There is limited utilisation of gastrointestinal ultrasonography (GIUS) in inflammatory bowel disease (IBD) by clinicians around the world. This study evaluated the benefits of IUS in IBD management from the patient's perspective and the value of GIUS in clinical decision-making. Methods: This was an observational, non-interventional cohort study investigating the real-world clinical management of patients (≥18 years of age) diagnosed with IBD. During routine outpatient consultations, patients were allocated to receive GIUS or not according to their clinical requirements. Patients completed self-reported questionnaires at study entry, immediately after their consultation and then at 4 and 16 weeks post-consultation. Clinicians reported disease activity status, therapeutic decisions and clinical management. Results: Patients (GIUS: 70 of 259[27%]; non-GIUS: 189 of 259[73%]) were aged 39.7 ± 12.8 years, 139 of 259 (54%) were male and 159 of 259 (61%) were diagnosed with Crohn's disease. Mean time since diagnosis was 9.4 ± 8.6 years for the GIUS group and 11.3 ± 9.1 years for the non-GIUS group. Immediately after undergoing GIUS, patients with active IBD reported significantly better understanding of all aspects of their disease and improved knowledge domain scores (all p values <0.05) vs. Non-GIUS patients (Table). Patients with active IBD undergoing GIUS reported significantly less adherence reduction over time ( p = 0.048). GIUS was the preferred imaging modality (comparing GIUS, MRI, CT, and colonoscopy) amongst patients who had undergone ≥2 imaging techniques (GIUS: 65%[34 of 52]; non-GIUS: 62% [59 of 95]). GIUS led to a change in management in more than half (38 of 70; 54.3%) of patients. For clinicians, GIUS changed assessment of IBD disease activity status in 15 of 68 (22.1%) patients, leading to management changes in 9 of 15 (60%) patients. Medication intensification was more likely in the GIUS vs. the Non-GIUS group (43% vs. 21%, p < 0.001). Even when stratified for disease activity, medication change was significantly more likely in the GIUS vs. the non-GIUS group ( p = 0.05). Conclusions: Use of GIUS improved clinicians' assessments of disease activity, and led to detection of more patients with active disease. It provided a valuable educational tool for patients and aided medication adherence. GIUS was the preferred investigative modality amongst IBD patients. GIUS provides a valuable, inexpensive and non-invasive tool that can contribute to improved outcomes in the ongoing care of patients with diagnosed IBD.